Perlindungan Hukum Jamaah melalui Pemulihan Aset dalam Kejahatan Travel Haji dan Umroh - Justicia Salsabilla; Slamet Tri Wahyudi (AHKAM, 2026)
The organization of Hajj and Umrah pilgrimage in Indonesia has both a sacred and strategic role for the religious sovereignty of society, but in practice it still faces problems of travel agency crimes and quota corruption that cause material and psychological losses for prospective pilgrims. This phenomenon indicates the urgency of optimizing national legal instruments through regulatory strengthening that is oriented not only toward punishing perpetrators but also toward holistic and comprehensive legal protection to ensure the fulfillment of citizens’ constitutional rights to perform worship with certainty and safety. This study aims to analyze asset recovery mechanisms in handling crimes related to the organization of Hajj and Umrah and to formulate juridical solutions for victim protection. This study used a normative juridical method with a statutory approach and a conceptual approach. Data were collected through literature study and analyzed descriptively-prescriptively with regard to legal norms, legal principles, and the synchronization of statutory regulations. The results show that the asset recovery mechanism under Law Number 31 of 1999 remains conventional and tends to be oriented toward the recovery of state finances, so it has not been able to provide fast and effective restitution for pilgrims who become victims because of lengthy and complex judicial procedures. This study recommends transforming the doctrine of asset recovery through the application of a non-conviction-based asset forfeiture mechanism and strengthening the role of authorities under Law Number 14 of 2025 so that assets derived from crime can be immediately seized and redistributed fairly to victims. The conclusion of the study emphasizes that strengthening asset recovery mechanisms and victim protection is an important prerequisite for realizing substantive justice in the organization of Hajj and Umrah pilgrimage.